DEVELOPMENT OF ULTRAVIOLET-SPECTROPHOTOMETRIC METHOD FOR ANALYSIS OF AMOXAPINE IN PHARMACEUTICAL DOSAGE FORM - Rangari, Shweta; Patil, Shraddha; Mahajan, Rutuja; Ahmed, Abrar; Raut, Nishikant A (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: Knowing the exact amount of active pharmaceutical ingredient (API) in pharmaceutical dosage form is of utmost importance to meet regulatory requirements and to ensure patient safety. Spectrophotometric analysis provides a simple, efficient, and economic approach for estimation of API in the pharmaceutical dosage form. In the present work, we have developed simple, sensitive, and highly economic ultraviolet (UV) spectrophotometric method for the estimation of amoxapine in a pharmaceutical formulation. Methods: Amoxapine shows maximum absorbance of light at wavelength 297 nm in water. The linearity study revealed that it obeys Beer-Lambert's law over the range of 2â€“20 Î¼g/mL. Absorptivity value of amoxapine was found to be 206.6Â±1.341. Result: The tablet formulation was successfully analyzed by developed UV spectrophotometric method. The developed method was validated as per International Conference on Harmonization guidelines with respect to accuracy, precision, specificity robustness . The limit of detection and limit of quantitation was found to be 19.8 and 60.50 ng/mL, respectively. Conclusion: The developed method is simple, precise, accurate, and cost-effective and can be used for routine analysis of amoxapine.